Increased Levels of S100A8/A9 in Patients with Peritonsillar Abscess: A New Promising Diagnostic Marker to Differentiate between Peritonsillar Abscess and Peritonsillitis. (17th October 2017) - Spiekermann, Christoph; Russo, Antonella; Stenner, Markus; Rudack, Claudia; Roth, Johannes; Vogl, Thomas
Abstract : Peritonsillar abscess (PTA) is a very frequent reason for urgent outpatient consultation and otolaryngological hospital admission. Early, correct diagnosis and therapy of peritonsillar abscess are important to prevent possible life-threatening complications. Based on physical examinations, a reliable differentiation between peritonsillar cellulitis and peritonsillar abscess is restricted. A heterodimeric complex called calprotectin consists of the S100 proteins A8 and A9 (S100A8/A9) and is predominantly expressed not only in monocytes and neutrophils but also in epithelial cells. Due to its release by activated phagocytes at local sites of inflammation, we assumed S100A8/A9 to be a potential biomarker for peritonsillar abscess. We examined serum and saliva of patients with peritonsillitis, acute tonsillitis, peritonsillar abscess, and healthy controls and found significantly increased levels of S100A8/A9 in patients with PTA. Furthermore, we could identify halitosis, trismus, uvula edema, and unilateral swelling of the arched palate to be characteristic symptoms for PTA. Using a combination of these characteristic symptoms and S100A8/A9 levels, we developed a PTA score as an objective and appropriate tool to differentiate between peritonsillitis and peritonsillar abscess with a sensitivity of 92% and specificity of 93%.